Родильно-хрестинні пісні: типологічна дивиргенція і завдання функційної реконструкції - Іваницький, А. (Народна творчість та етнографія, 2009)
The musical typology of birth and baptize celebration which is not noted by rhythm- structure unity is typical for calendar and wedding party”s tunes. It can be explained by domination of ritualethnographic bases. In the birth and baptize ethnographic complex lullaby melodies take a very important place. As Ukrainian birth–baptize songs are not well studied and reflected in the special literature, the task of the complex investigation of ritual ethnography is demanded.